Penerapan Model Pembelajaran Role Playing dalam Mata Pelajaran Bahasa Indonesia Kelas 6 SD di Daerah 3T - Arien Cahyani Putri; Luthfi Fadilah; Nur Syamsiyah (Universitas Muhammadiyah Jember, 2022)
This study discusses the problem of the low quality of education in the 3T area caused by the incompatibility of the learning model with children's abilities, environmental conditions, facilities, media, and teaching materials. Therefore, it is necessary to use a role playing learning model, especially in Indonesian subjects at the elementary school level in the 3T area, which can adapt to conditions in the 3T area. Role playing models can take advantage of media in the surrounding environment to help students follow the learning process in schools that lack facilities and infrastructure. This study aims to determine the condition of education in Elementary Schools in the 3T area and apply the role playing learning model in the 3T area in the subject matter of Indonesian class 6 of elementary school. This study uses a qualitative descriptive method, data collection through interviews with students who become teaching volunteers in the 3T area and literature study. This study indicates that the three schools located in the 3T area have similarities and differences in problems that are the factors causing the low quality of elementary school education in the 3T area. The factors that have been identified are the distance from where the teacher lives, the quality of the teacher, facilities and infrastructure, students' reading ability, electricity in schools, public awareness, and teaching materials. The role playing model in Indonesian class 6 SD can be used for students in the 3T area. In its implementation, it must be carried out in stages, starting with introducing the model to students.